2019
DOI: 10.1016/j.pmedr.2019.100840
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a family-focused YMCA-based diabetes prevention program in youth: The E.P.I.C. Kids (Encourage, Practice, and Inspire Change) Study

Abstract: Efficacious lifestyle modification programs for children at risk of type 2 diabetes (T2D) have not been well established outside of clinical settings. In this study, the feasibility of a family-focused, YMCA-based prevention program for children at risk of T2D was evaluated between September 2015 and July 2016 in Tucson, Arizona. A 12-week YMCA-led lifestyle intervention was adapted for 9–12-year-old children and their families to encourage healthy eating, physical activity, and supportive home environments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…These findings will inform the development of targeted nutrition education focused on the energy density of foods, how to choose tasty low-calorie beverages and drink less sugary drinks, how to find the best items at the grocery store or convenience store, for example. Targeted nutrition education in a family-focused diabetes prevention program for diverse youths aged 9–12 y has been successfully implemented (20, 21). These findings also support the need to incorporate more native traditional approaches (22) and foods including plant-based diet interventions, historically staple foods for native people.…”
Section: Discussionmentioning
confidence: 99%
“…These findings will inform the development of targeted nutrition education focused on the energy density of foods, how to choose tasty low-calorie beverages and drink less sugary drinks, how to find the best items at the grocery store or convenience store, for example. Targeted nutrition education in a family-focused diabetes prevention program for diverse youths aged 9–12 y has been successfully implemented (20, 21). These findings also support the need to incorporate more native traditional approaches (22) and foods including plant-based diet interventions, historically staple foods for native people.…”
Section: Discussionmentioning
confidence: 99%
“…In public health practice, successes have been seen in familycentered programming for traditional public health problems, such as poor nutrition, diabetes prevention, and adolescent risk-taking behaviors that contribute to HIV. Multiple studies have demonstrated that when family practices, values, and responsibilities are included in public health interventions, there is a much higher likelihood of positive change for both individuals and families and lasting success (28)(29)(30). Programs like Healthy Home Offerings via the Mealtime Environment Plus Higher scores denote more family support and involvement in programs.…”
Section: Discussionmentioning
confidence: 99%
“…(HOME Plus) or Strong African American Families (SAAF) are examples of programs that work with families to promote healthy eating habits in childhood to prevent obesity in adulthood. Evaluations of these programs have shown significant and sustained healthy eating habits for individual family members while also creating a healthier food environment in family homes (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable efforts are underway to take diabetes prevention programs to scale, 13,[17][18][19] and increasing insulin sensitivity is an important physiologic target for health promotion among populations at high risk. 20 Therefore, it is critical to identify biologically relevant estimates of insulin sensitivity that can be practically applied within the context of population health.…”
Section: Discussionmentioning
confidence: 99%